Searching for Axion Dark Matter Gegenschein of the Vela Supernova Remnant with FAST - Wenxiu Yang; Yitian Sun; Yougang Wang; Katelin Schutz; Yichao Li; Calvin Leung; Wenkai Hu; Shuanghao Shu; Kiyoshi Masui; Xuelei Chen (The Astrophysical Journal)
Axions are one of the leading dark matter candidates. If we are embedded in a Milky Way dark matter halo comprised of axions, their stimulated decay would enable us to observe a counterimage (“axion gegenschein”) with a frequency equal to half the axion mass in the opposite direction of a bright radio source. This spectral line emission will be broadened to Δ ν / ν  ∼  σ _d / c  ∼ 10 ^−3 due to the velocity dispersion of dark matter, σ _d . In this pilot study, we perform the first search for the expected axion gegenschein image of Vela supernova remnant with 26.4 hr of effective ON–OFF data from the Five-hundred-meter Aperture Spherical radio Telescope (FAST) L -band (1.0–1.5 GHz) 19 beam receiver. Our null detection limits the axion–photon coupling strength to be g _aγγ  ≲ 2 × 10 ^−10 GeV ^−1 in the mass ranges of 8.7 μ eV ≤ m _a ≤ 9.44 μ eV and 10.85 μ eV ≤ m _a ≤ 12.01 μ eV. These results provide a stronger constraint on g _aγγ in this axion mass range than the current limits obtained by the direct search of an axion decay signal from a dwarf galaxy that uses FAST observations, but are a factor of ∼3 times weaker than the current CERN Axion Solar Telescope limit. Based on our observation strategy, data processing methods, and results, the expected sensitivity will reach ∼10 ^−11 GeV ^−1 with ∼2000 hr of observation in the future.